Atlas of intestinal pathology. Neoplastic diseases of the intestines / Volume 1, (2019) - Li-Chang, Hector H; Kirsch, Richard; Conner, James; Sari, Aysegul; Pollett, Aaron; El-Zimaity, Hala; Jain, Dhanpat; Celli, Romulo; Reid, Stephanie L; Riddell, Robert H
No abstract available